CONTAMINATION OF IRRIGATION CANALS AND ITS IMPACT ON HUMAN BEINGS AND LIVE STOCK - Mantena, Jagapathi Raju; Penmetsa, A.R.K. Raju; Vallabhaneni, Vanisree; Popuri, Raghu Ram; Tenneti, Rambabu; Kondepudi, Niharika (IJRDO - Journal of Mechanical And Civil Engineering, 2016)
Water pollution has emerged as an important issue in India as most of the rivers are polluted, which are having substantial negative impact on human health and aquatic life. Heavy metals are potentially toxic to crop plants, animals and human beings. 90%of infectious diseases in developing countries are transmitted through polluted water. Western Delta of West Godavari is based on canal water for drinking, domestic and irrigation purposes. This is the source of drinking water for livestock also. Being deltaic area, soil is fertile and due to availability of plenty of water, intensive agriculture, intensive aquaculture, Poultry farms are functioning throughout the year. In Western Delta of West Godavari, there are six irrigation canals- Venkayya-Vayyeru, Eluru canal, Narsapur canal, Gostani-Velpuru canal, Kakaraparru and Right Bank canal and Attili canal. Water samples were collected from all these canals for two seasons and analyzed for physico- chemical and biological parameters like pH, TDS, EC, TH, TA, Turbidity,NH3, NO2, NO3,Na,K , Cl ,DO,BOD, COD, TBC and E.Coli to understand the present status of the contamination of these canal waters. The assessed data also used to compare the concentration variation contaminants in winter and rainy seasons. Deltaic water is highly contaminated and not suitable for its consumption by humans and livestock